Evaluation of Service Continuity Management: University of Costa Rica, Western Headquarters - Campos Pérez, Lisa (2021)
The University of Costa Rica (UCR) is one of the five public universities of the Republic of Costa Rica, the Western Headquarters (UCR-SO) was the first regional headquarters of the UCR, founded in 1968. In recent years the development of university activities and the use of its facilities have suffered due to different phenomena that have affected the institution. The purpose of the document is to evaluate the development level of the continuity strategies of the UCR-SO, through the analysis of the risk management systems and the essential service continuity of the institution. Under the audit of five international standards and internal factors of the institution which seeks to identify improvement opportunities in relation to the Institutional Continuity of the UCR-SO. Obtaining as a result the little development of the evaluated management systems and the need that the institution features to generate and integrate a model ensuring the timely and quality provision of these services, especially in essential services due to their effect in educa-tional, social and investigative development; as well as in the effective operation of the institution. JEL: I23 Higher Education andresearch institutions.